The Role of PET-CT in the Differential Diagnosis of Malignant-Paramalignant Pleural Effusion - Bülent Akkurt; Elif Torun Parmaksız; Coşkun Doğan; Seda Beyhan Sagmen; Nesrin Kıral; Ali Fidan; Saadet Akkus; Sevda Şener Cömert (Southern Clinics of Istanbul Eurasia, 2019)
INTRODUCTION[|]Pleural effusion is an important problem in cancer patients as it will affect the stage, prognosis and treatment. Therefore, it is necessary to distinguish between paramalignant and malignant effusions. In this study, we aimed to investigate the role of PET-CT in the evaluation of pleural effusion.[¤]METHODS[|]Patients diagnosed with malignancy and associated pleural effusion and evaluated by PET-CT were prospectively included in this study. SUDmax values of pleural fluid were recorded in consideration of the demographic information and PET-CT findings. In all patients, biochemical parameters, including glucose, LDH, albumin and total protein and pH values of the pleural fluid obtained by thoracentesis, were measured. All pleural fluid samples were sent for cytological evaluation. After cytological evaluation, patients were defined as having malignant or paramalignant pleural effusion and accordingly divided into two groups. The t-test was used to compare SUDmax values between the groups. A chi-square test was used to compare categorical data.[¤]RESULTS[|]A total of 69 patients (30 women [43%] and 39 men [57%]) with a mean age of 63.55 (37–88) years were included in this study. The cytological analysis revealed malignant pleural effusion in 53 patients. In the follow-up of 16 patients, pleural fluid was accepted as of paramalignant nature due to the absence of both atypical cells in the fluid cytology and also clinical findings favoring malignancy. The mean SUDmax value was found to be 1.43 in paramalignant fluids and 1.5 in malignant fluids but without any statistically significant difference. Malignant cytological findings were detected despite the absence of FDG involvement in 23 (33%) cases, including patients with lung cancer (n=13), mesothelioma (n=3), breast cancer (n=2), colon cancer (n=2), ovarian cancer (n=1), gastric cancer (n=1), or endometrial cancer (n=1). PET had a sensitivity of 56.6% and a specificity of 50% in the detection of malignant pleural effusions with a 78.9% positive, and 25.8%negative predictive value.[¤]DISCUSSION AND CONCLUSION[|]Distinguishing between malignant and paramalignant effusions according to FDG uptake in pleural fluids may cause misleading results. Therefore, we suggest that advanced diagnostic procedures should be used in cases where the presence of malignant fluid will change the clinical approach.[¤]